PENGARUH PH PLAK TERHADAP ANGKA KEBERSIHAN GIGI DAN ANGKA KARIES GIGI ANAK DI KLINIK PELAYANAN ASUHAN POLTEKKES PONTIANAK TAHUN 2013 - Sri Rezki; Pawarti . (ODONTO : Dental Journal, 2014)
Background: Dental plaque is a thin layers composed of various microorganisms which is formed on teeth surface after contacted with saliva in several minutes. Dental plaque is not dental disease but can be cause dental caries and periodontal disease and others teeth and mouth diseases.The relation of dental plaque and dental caries is on the plaque acidity that tend to email and dentine demineralisation, which will cause dental caries.Research purpose was to investigate influence dental plaque to oral hygiene index and dental caries index on child at the poltekkes dental clinic in pontianak 2013.Method: Research at the poltekkes pontianak dental clinic in may 2013. subject of study consisted of 32 patients child. 20 children of the female and 13 children of the male s. this research is research quantitative with the approach of observation and cross sectional methode. Result: The result, Ph dental plak is not significant relation with oral higiene index and caries index. Conclusion: caries caused multifaktorial so the prevention of various terms need to be done.Keywords: pH dental plaque, oral higiene index, dental caries index